Expanding the field of view: Design considerations for a sparse-regular FFT SKA radio telescope - De Vaate, J.; Davidson, David; Benthem, P. (2017)
© 2017 IEEE. This paper proposes a system approach to explore the full potential of phased arrays with sparse, regular spacing for radio astronomy. In particular, the FFT telescope is revisited, with its tantalising promise of instantaneous (nearly) all sky observations.